Synchronizing gait with cardiac cycle phase alters heart rate response during running - Constantini, K.; Stickford, A. S. L.; Bleich, J. L.; Mannheimer, P. D.; Levine, B. D.; Chapman, R. F. (Medicine & Science in Sports & Exercise, 2018)
Timing foot strike to occur in synchrony with cardiac diastole may reduce left ventricular afterload and promote coronary and skeletal muscle perfusion.